2020
DOI: 10.1113/jp280439
|View full text |Cite
|
Sign up to set email alerts
|

The critical closing pressure contribution to dynamic cerebral autoregulation in humans: influence of arterial partial pressure of CO2

Abstract: Dynamic cerebral autoregulation (CA) is often expressed by the mean arterial blood pressure (MAP)-cerebral blood flow (CBF) relationship, with little attention given to the dynamic relationship between MAP and cerebrovascular resistance (CVR). r In CBF velocity (CBFV) recordings with transcranial Doppler, evidence demonstrates that CVR should be replaced by a combination of a resistance-area product (RAP) with a critical closing pressure (CrCP) parameter, the blood pressure value where CBFV reaches zero due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 57 publications
5
30
1
Order By: Relevance
“…31,54,57 In a recent study, SRV CrCP , but not SRV RAP , explained the corresponding changes in SRV CBFV in response to hypercapnia. 26 In this study, estimates of SRV RAP (Figures 3(b) and 5(b)) were in broad agreement with previous estimates of RAP, or CVR response to a step change in MAP, 14,15,54,58 remembering that in our case the SRV RAP curves are inverted, to represent the corresponding reduction in V CBFV , following a rise in RAP. What has not been described previously though, is how the SRV RAP temporal pattern varies with the efficiency of dynamic CA (Figure 5(b)) and the linear association of the SRV RAP with ARI at T2 (Table 2), and both ARI and age at T3 (Table 2, Figure 5(b)).…”
Section: Mechanisms Of Cbf Regulationsupporting
confidence: 90%
See 4 more Smart Citations
“…31,54,57 In a recent study, SRV CrCP , but not SRV RAP , explained the corresponding changes in SRV CBFV in response to hypercapnia. 26 In this study, estimates of SRV RAP (Figures 3(b) and 5(b)) were in broad agreement with previous estimates of RAP, or CVR response to a step change in MAP, 14,15,54,58 remembering that in our case the SRV RAP curves are inverted, to represent the corresponding reduction in V CBFV , following a rise in RAP. What has not been described previously though, is how the SRV RAP temporal pattern varies with the efficiency of dynamic CA (Figure 5(b)) and the linear association of the SRV RAP with ARI at T2 (Table 2), and both ARI and age at T3 (Table 2, Figure 5(b)).…”
Section: Mechanisms Of Cbf Regulationsupporting
confidence: 90%
“…31,53 Although hypercapnia induces significant increases in CBFV and depression of CA, the contribution of RAP to explain these changes has been minimal or entirely absent. 23,26,54 Moreover, time-varying changes in RAP have been closely associated with a response to preceding changes in MAP, and not with EtCO 2 25,.25,31,55,56 On the other hand, different authors have reported a strong association between CrCP and PaCO 2 16,23 and dynamic analyses have also shown that CrCP could explain better the changes in CBFV resulting from neural stimulation than RAP. 31,54,57 In a recent study, SRV CrCP , but not SRV RAP , explained the corresponding changes in SRV CBFV in response to hypercapnia.…”
Section: Mechanisms Of Cbf Regulationmentioning
confidence: 95%
See 3 more Smart Citations